Near-optimal data detection for two-dimensional ISI/AWGN channels using concatenated modeling and iterative algorithms - Xiaopeng Chen; Chugg, K.M. (1998 IEEE International Conference on Communications, 1998)
The general problem of performing digital data detection for a two-dimensional (2D) systems is considered with the specific application of page-access optical memory systems in mind. A simple 2D intersymbol interference (ISI) channel with additive white Gaussian noise (AWGN) is assumed. An equivalent signal model consisting of two one-dimensional systems separated by a block interleaver is developed and used to motivate the application of previously developed algorithms for data detection in concatenated systems. The resulting iterative detection algorithms, which are based on soft-output algorithms, are demonstrated to achieve near-optimal performance even for very severe 2D ISI channels.